HEATING THE HOTEL "ZHULHANY" IN KIEV DUE TO THE USE OF RENEWABLE ENERGY SOURCES - Демченко, Є.; Маслюкова, З.; Новицька, Є. (Science-based technologies, 2010)
Technical schemes of combined use of traditional and renewed energy sources for heating and hot water supply of hotel «Zhulyany» in the city of Kyiv are offered. Technological parametres of the offered schemes are calculated and their power efficiency is defined. It is shown that from the power point of view the scheme on the basis of use of the underground accumulator in water-bearing horizon and a peak gas copper is perspective for practical introduction.